Peran Orang Tua, Lingkungan Pergaulan dan Konsep Diri Terhadap Kenakalan Remaja di Kelurahan Graha Inda - Ni Nyoman Murti; Sonya Yulia S (Husada Mahakam, 2021)
Abstract Juvenile delinquency is an important issue today. Indonesia is one of the countries that have high juvenile delinquency. The purpose of this study is to know the influence of parenthood, social environment, and self-concept on juvenile delinquency in Graha Indah Balikpapan Village. The research design is cross-sectional by using analytical descriptive research with Observational Survey. Samples in this study as many as 95 teenagers in Graha Indah Village using precision proportion formula. Data analysis using simple linear regression test and Multiple Linear Regression analysis. The results showed there is an influence of the role of parents on juvenile delinquency with a value of p-value 0.000, There is an influence of the social environment on juvenile delinquency with a value of p-value 0.000, There is an influence of self-concept on juvenile delinquency with a value of p-value of 0.000. There is an influence of parental role, social environment, and self-concept on juvenile delinquency with a value of p-value of 0.000. To provide education to adolescents related to juvenile delinquency, the importance of parental roles and environmental roles, and community roles to prevent delinquency in adolescents. Keywords : Teenager, Parent role, Social environment ,self concept, delinquency Teen